Protection Coordination Practices for Industrial Ring Distribution Network Case Study of Organized Industrial Zone (GEBZE, Turkey) - Shobole, Abdulfetah; Baysal, Mustafa; Wadi, Mohammed; Tur, Mehmet Rida (IEEE, 2018)
The traditional distribution networks are mostly radial. Radial networks are easy to implement and operate, but it introduces a great challenge concerning electricity supply reliability. In organized industrial zones, the unplanned energy interruptions can cost a lot, as industrial loads are always working. Consequently, distribution networks are mostly implemented as a ring network. The ring distribution network improves the electricity supply reliability. However, compared to the radial networks, the application of ring network introduces its own technical challenges such as increased short circuit current during the fault, difficulty in protection coordination, increased rating capacity of each equipment and increased investment cost. In this paper, the protection coordination technique that is used in an organized industrial zone will be discussed. In the ring distribution network, differential relays, which rely on communication between the protection relays, are used for the underground cable protection. To guarantee cable protection when communication is failed, an auxiliary protection by using directional overcurrent relays is used. In this paper, the protection coordination study for the GEBZE organized industrial zone, which is available in Istanbul, Turkey, is conducted by using state of the art methods. The results of the study are verified by applying to ABB relays, which are available on the organized industrial zone's site under study.
Keywords: Differential protection; earth fault protection; organized industrial zones; overcurrent protection; radial networks; ring networks; Science & Technology - Other Topics; Energy & Fuels; Engineering